Sustainable Highway Design: Disentangling the Effects of Geometric-Related and Traffic-Related Factors on Urban Highway Traffic Emissions - Xue Bing; Quanlun Wei; Jian Lu; Chaoyang Li; Yi Zhang (Advances in Civil Engineering)
Reducing highway traffic emissions, which is a major part of China's total transportation-related emissions, is a key to China's sustainable development. However, the effects of geometric-related and traffic-related factors on highway traffic emissions are rarely studied in China. Employing data collected from Cao'an Highway in Shanghai, China, and Traffic Software Integrated System (TSIS) as a simulation tool, this paper analyzed the effects of three geometric-related factors and one traffic-related factor on three traffic emissions (HC, CO, and NOx). The geometric-related factors are lane width, number of vehicle lanes, and intersection lane configuration, and the traffic-related factor is free-flow speed. The results indicated that (1) widening the lane width may cause the increase of CO emissions, (2) increasing the number of vehicle lanes may result in the decrease of all three emissions, (3) intersection lane configuration has significant influence on traffic emissions, and (4) the average speed of 23-24 mph is associated with the lowest traffic emissions. The research findings will facilitate the understanding on effects of various factors on highway traffic emissions and provide insights for policy-makers, scholars, and engineers into the improvement of sustainable highway design and management.